2013
DOI: 10.1002/pc.22621
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength of polymer lightweight aggregate concrete

Abstract: Bond strength, physical, and mechanical properties of lightweight PC were investigated with inclusion of pumice lightweight aggregate in maximum size of 12 mm. As binder material, epoxy resin‐based polymer was used with its hardener. The binder to aggregate ratio was 30% by weight. In addition, steel fibers were added to lightweight PC mixtures in ratio of 0, 0.5, and 1%. After lightweight PC mixture was prepared, it was poured in the molds with different type of steel‐bars in size of 100 × 100 × 100 mm3. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Uygunoglu et al [32] reported that lightweight polymer concrete with pumice aggregate has a unit weight of 1346 kg/m 3 . Although these values are great, lightweight polymer concrete has a few disadvantages such as its cost which is very high and very low heat and fire resistance.…”
Section: Bulk Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Uygunoglu et al [32] reported that lightweight polymer concrete with pumice aggregate has a unit weight of 1346 kg/m 3 . Although these values are great, lightweight polymer concrete has a few disadvantages such as its cost which is very high and very low heat and fire resistance.…”
Section: Bulk Densitymentioning
confidence: 99%
“…Pumice has been widely used to produce lightweight concrete [26,[31][32][33]. However, very limited information on the usage of pumice as pore maker in fired clay brick production has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic modulus of elasticity of specimens was calculated depending on ultrasonic pulse velocity by Eq. (1) at 7 day-aged specimens 30 …”
Section: Tests On Polymer Compositesmentioning
confidence: 99%
“…The half-open porous structure of pumice aggregates mostly causes the increase of compressive strength by improving the adherence between the binder and the aggregate. However, because of the half-open surface structure of pumice, the polymer concrete (PC) needs more binding material than a PC with a normal aggregate [2] . Some researches have stated that the different mechanical features found in polyester-based PCs are related to the type of thermosetting resin or mineral aggregates, and to their concentrations in composite [3] .…”
Section: Introductionmentioning
confidence: 99%